Comparative Response of Arbuscular Mycorrhizal Fungi versus Endophytic Fungi in Tangor Citrus: Photosynthetic Efficiency and P-Acquisition Traits - Yang Lü; Wei-Jia Wu; Ming-Yu Zhu; Zi-Yi Rong; Tian-Zhi Zhang; Xin-Ping Tan; Ying He; Mashael Daghash Alqahtani; Suresh Kumar Malhotra; Anoop Kumar Srivastava; Qiang-Sheng Wu (Horticulturae, 2024)
Citrus plants are prone to phosphorus (P) deficiency, especially in acidic soil, making them more dependent on root-associated endophytic fungi for growth and development. Beni-Madonna, a hybrid of Citrus nanko × C. amakusa, is a citrus known as “tangor” that is highly popular in China and other parts of the world due to its deep red color and jelly-like flesh. In this study, the inoculation response to two arbuscular mycorrhizal fungi (Diversispora versiformis, Dv; Funneliformis mosseae, Fm) and an endophytic fungus (Serendipita indica, Si) with regard to the growth, leaf gas exchange, light energy efficiency, P levels, acid phosphatase activity, and expression of the purple acid phosphatase (PAP) and phosphate transporter (PT) genes through a potted experiment using Beni-Madonna (tangor) citrus plants grafted on trifoliate orange (Poncirus trifoliata) was studied. Two years following inoculation, the root fungal colonization rates of inoculated plants were significantly increased, accompanied by an increase in plant height and stem diameter, with Si presenting the best effect. Fungal inoculations also significantly increased the leaf chlorophyll index, nitrogen-balance index, photosynthesis rate, stomatal conductance, transpiration rate, photosynthetic efficiency, and quantum yield of PSII, while it reduced photoinhibition and heat dissipation, with Si having the best effect on light energy efficiency. Si significantly increased leaf and root P levels, as well as root CsPAP1‒3, CsPT2, CsPT3, and CsPT7 expression and soil acid phosphatase activity; Fm in mycorrhizal fungi significantly increased leaf and root P levels, as well as root CsPT1 and CsPT7 expression and root/soil acid phosphatase activity. These observations suggested an advantage of Si over the other two AMF in terms of improved plant growth and P acquisition, while Fm displayed prominent effects on increased photosynthetic efficiency.